(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
For many families, the idea of going out for walks and family adventures can be a dream that is erased by the determination of autistic spectrum in a child. Gaps in the health and quality of life of young people with autism spectrum disorder (ASD) are well documented. One particularly noticeable gap that affects both physical health and quality of life is in the area of outdoor recreation, particularly including outdoor recreation activities such as biking, hiking, running, canoeing/kayaking, horseback riding, and skiing. Of the many outdoor activities to promote physical fitness, hiking is perhaps the most versatile and accessible for people with ASD. Hiking is a natural extension of walking. It is one of the first skills we acquire, one of the most important activities in everyday life and one of the few forms of recreation that does not require specific equipment and conditions. On the other hand, except for perhaps the most densely populated urban areas, there are almost always trails nearby. Lately even urban hikes that move around the city are becoming more and more popular. Whether you’re climbing the mountains at an expert level or hiking a trail, hiking gets your kids moving, which is of utmost importance in our modern society, when childhood seems to be filled more and more with time spent in front of the screens, and for children with autism this can become a serious problem. The main goal of this paper, on the one hand, is to increase awareness of the importance of hiking for psychophysical health, both for people from the general population and for people with ASD, but also to give recommendations for the approach and the way of organizing hiking activities for people with ASD, on the other hand.